BHMN PT: ANTARA IDEALISME, KAPITALISME, DAN LIBERALISME - Fahri, Muh (Jurnal Bestari, 2008)
State Owned Legal Enterprise status (PT BHMN) which is hoped to be the leader in improving the national education quality has not proven the satisfied achiement. In the contrary, it obscurcs both students and people. Since its changing status, it applies many educational fees which significantly rise. Thus, PT BHMN seems to shift its function and vision that education is the goverment's responsibility and it is not a profit organozation. In turn, the cost of education brings PT BHMN trapped in capitalism, liberalism and commercialism which is not in line with the idealism of higher education.